新型少齿差减速器传动系统可靠性分析及结构集成设计 - 郭小林; 王家序; 肖科; 李敏 (Jixie chuandong)
Pertaining to a new type planetary gear drive with small teeth number difference system,considered the effects of the motor,reducer and the couplings to the system,the reliability model and fault tree mode of the system are established. Then by quantitative and qualitative analysis,the weaknesses of the system are found out. Finally the effective methods are presented to improve the reliability of the system. And the analysis results are checked and evaluated to provide a reference for related structure design and reliability study.